Pollen storage of coconut dwarf accession Chowghat Orange Dwarf at low temperature - VELURU, APARNA; PRAKASH, KRISHNA; NEEMA, M; MURALIKRISHNA, K S; SAMSUDEEN, K; CHANDRAN, K P; RAJESH, M K; KARUN, ANITHA (The Indian Journal of Agricultural Sciences, 2021)
Pollen collection and storage assume importance in hybridization programs in coconut. Development of an effective short-term storage method for coconut pollen ensures availability of pollen for coconut breeding throughout the year. In the present study, pollen collected from dwarf coconut cultivar Chowghat Orange Dwarf (COD), using standardized extraction procedures, was utilized for studying their storage behaviour under four different low-temperature regimes, i.e. 4ºC, -20ºC, -45ºC and -196ºC along with control at room temperature. Data on pollen germination percentage and pollen tube lengths were collected based on in vitro procedures at four different storage intervals (1st day, 14th day, 30th day and 60th day) to identify best short-term storage temperature. Germination percentage of pollen gradually reduced with duration of storage in all treatments but in case of pollen, which was stored at room temperature (control, i.e. 28±2ºC), viability decreased drastically and became nil within two weeks. Results revealed that higher germination percentage (38.82%) and pollen tube length (535.9 μm) were observed at -196ºC followed by -45ºC (31.77%, 400.73 μm) and -20ºC (30.82%, 282.89 μm) after a storage period of eight weeks. This study shows that desiccated pollen grains can be successfully stored at -45ºC for its utilization in breeding programmes besides long term storage at -196ºC.